KAJIAN TINGKAT PENERAPAN GREEN CONSTRUCTION PADA PROYEK KONSTRUKSI GEDUNG FASILITAS PENDIDIKAN DI JAWA TIMUR - Laila, Nurul Alfi Candra; Wiryasuta, I Ketut Hendra; Hardiyanti, Siska Aprilia (Jurnal Teknik Sipil Giratory UPGRIS, 2023)
The construction of educational facilities in Indonesia, especially in East Java, are increase. However, this development has an environmental impact due to construction activities that use heavy equipment, produce material waste, and are less efficient in managing energy. To reduce this impact, it is important to implement green construction. The purpose of this research is to assess the level of green construction. The Model Assessment Green Construction (MAGC) method is used to assess the level of green construction implementation, focusing on environmentally friendly construction criteria and related indicators. The data from the questionnaire results, evaluating the weights of aspects and factors, were processed using the Analytical Hierarchy Process (AHP) method, resulting in aspect weight of 0.336 and factor weight of 0.821. These weight values become multiplier factors in the MAGC calculation. The results of the MAGC calculation obtain a percentage of 36% from 11 educational facility building construction projects in East Java that meet the NGCIdeal criteria within the baseline range of 15.47 to 21.92.